MS2 virus inactivation by atmospheric-pressure cold plasma using different gas carriers and power levels - Wu, Yan (2015)
In this study, airborne MS2 bacteriophages were exposed for subsecond time intervals to atmospheric-pressure cold plasma (APCP) produced using different power levels (20, 24, and 28 W) and gas carriers (ambient air, Ar-O2 [2%, vol/vol], and He-O2 [2%, vol/vol]). In addition, waterborne MS2 viruses were directly subjected to the APCP treatment for up to 3 min. MS2 viruses with and without the APCP exposure were examined by scanning electron microscopy (SEM), reverse transcription-PCR (RT-PCR), and sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). Viral inactivation was shown to exhibit linear relationships with the APCP generation power and exposure time (R(2) > 0.95 for all energy levels tested) up to 95% inactivation (1.3-log reduction) after a subsecond airborne exposure at 28 W; about the same inactivation level was achieved for waterborne viruses with an exposure time of less than 1 min. A larger amount of reactive oxygen species (ROS), such as atomic oxygen, in APCP was detected for a higher generation power with Ar-O2 and He-O2 gas carriers. SEM images, SDS-PAGE, and agarose gel analysis of exposed waterborne viruses showed various levels of damage to both surface proteins and their related RNA genes after the APCP exposure, thus leading to the loss of their viability and infectivity.